Patients treated for acute headache with intranasal droperidol spend less time in the emergency department: A retrospective observational study. (14th May 2022) - Stern, Ari; Munro, Andrew; King, Chris; Knight, Amy; Bruce, Emily; Stacey, James; Hammond, Siggi; Holland, Amy
Abstract: Objective: Headache is a common presenting complaint to the ED. Using time from the first provider to discharge as a surrogate for effectiveness, we aimed to determine if intranasal (IN) droperidol is as beneficial as usual treatment for acute headache in the ED. Methods: There were 1213 consecutive presentations of adults with acute headache over a 42‐month period. Electronic records for each event were interrogated, 406 events met pre‐determined exclusion criteria. Of the remaining 805 eligible patient events, 139 received IN droperidol, whereas 666 were given usual therapy. Results: There was a 20 min reduction of mean and median ED length of stay (LOS) for the group that got treated with IN droperidol. Conclusions: IN droperidol reduced LOS in the ED. There are potential cost savings of this effective treatment via this novel route. A prospective multi‐centre study of the use of IN droperidol for the treatment of acute headache in the ED is recommended.